Quantitative Profiling of Chromatome Dynamics Reveals a Novel Role for HP1BP3 in Hypoxia-induced Oncogenesis - Dutta, Bamaprasad (Mol Cell Proteomics, 2014)
In contrast to the intensely studied genetic and epigenetic changes that induce host cell transformation to initiate tumor development, those that promote the malignant progression of cancer remain poorly defined. As emerging evidence suggests that the hypoxic tumor microenvironment could re-model the chromatin-associated proteome (chromatome) to induce epigenetic changes and alter gene expression in cancer cells, we hypothesized that hypoxia-driven evolution of the chromatome promotes malignant changes and the development of therapy resistance in tumor cells. To test this hypothesis, we isolated chromatins from tumor cells treated with varying conditions of normoxia, hypoxia, and re-oxygenation and then partially digested them with DNase I and analyzed them for changes in euchromatin- and heterochromatin-associated proteins using an iTRAQ-based quantitative proteomic approach. We identified a total of 1446 proteins with a high level of confidence, including 819 proteins that were observed to change their chromatin association topology under hypoxic conditions. These hypoxia-sensitive proteins included key mediators of chromatin organization, transcriptional regulation, and DNA repair. Furthermore, our proteomic and functional experiments revealed a novel role for the chromatin organizer protein HP1BP3 in mediating chromatin condensation during hypoxia, leading to increased tumor cell viability, radio-resistance, chemo-resistance, and self-renewal. Taken together, our findings indicate that HP1BP3 is a key mediator of tumor progression and cancer cell acquisition of therapy-resistant traits, and thus might represent a novel therapeutic target in a range of human malignancies.